2020
DOI: 10.1007/s13760-020-01280-y
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of the children with hydrocephalus

Abstract: The objective of the study was to examine selected aspects of the functioning of children treated for hydrocephalus, with particular emphasis on their degree of independence. Analysis of the medical records of patients treated for hydrocephalus in the Department of Pediatric Neurosurgery in Katowice in 2000-2010. The Barthel scale was used to assess the children's independence. Information on the children's functioning was obtained directly from their parents using a questionnaire developed by the author. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(27 reference statements)
1
3
0
2
Order By: Relevance
“…17 On the contrary, another study focused on functional outcome indicated that patients with hemorrhagic hydrocephalus were the least dependent according to the Barthel scale. 2 Similar results were presented by Gmeiner et al, who revealed that etiology of hydrocephalus was linked to degree of patient independence in adulthood (with worst results in the group with MMC). 21 In the large population-based study by Schmidt at al., no association was observed between school performance and age at diagnosis of hydrocephalus or number of surgical procedures performed.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…17 On the contrary, another study focused on functional outcome indicated that patients with hemorrhagic hydrocephalus were the least dependent according to the Barthel scale. 2 Similar results were presented by Gmeiner et al, who revealed that etiology of hydrocephalus was linked to degree of patient independence in adulthood (with worst results in the group with MMC). 21 In the large population-based study by Schmidt at al., no association was observed between school performance and age at diagnosis of hydrocephalus or number of surgical procedures performed.…”
Section: Discussionsupporting
confidence: 79%
“…In the work of Szefczyk-Polowczyk and Mandera, the parents of 8 children with hydrocephalus (of 90 patients older than 6 years) reported lack of participation in PE classes. 2 Comparison with this result is difficult because that study did not assess return to sport participation itself, and the parents had the opportu- nity to give any answer when asked about school problems in general. Our data need to be considered within the context of the group enrolled in our study, because we initially excluded children who were unable to attend PE classes because of their poor neurological status or profound intellectual disability.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to the previously mentioned ACM, we had only a minority, nine children (3.5%), with these types of disorders (i.e., neuromotor, somatosensory, and coordination problems). Impaired cerebrospinal fluid circulation, including hydrocephalus, also seems to play a minor role in our group of patients (2/257) [ 30 ]. In pediatric vertigo cases with an alteration of consciousness, an EEG should be done to rule out epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Juga terdapat gangguan belajar, keterbatasan interaksi dengan teman sebaya dan rendahnya rasa percaya, yang semuanya menjadi masalah yang harus dihadapi orang tua dan penyedia layanan sosial atau kesehatan. 16 Usia saat pemasangan shunt berkorelasi negatif dengan semua skor HOQ, yang menunjukkan bahwa pemasangan yang lebih dini akan menyebabkan luaran QoL lebih baik. Namun, jarak waktu antara diagnosis dan VP shunt tidak berkorelasi negatif dengan skor HOQ, sedangkan jarak waktu antara VP shunt dan pemeriksaan HOQ menunjukkan korelasi positif yang bermakna dengan beberapa sub-skor (keseluruhan dan sosial-emosional), yang berarti terjadi perbaikan QoL setelah pemasangan shunt.…”
Section: Pembahasanunclassified
“…Meski demikian, telah dilakukan eksklusi terhadap abnormalitas kongenital kompleks yang berdasarkan penelitian terdahulu menyebabkan luaran paling buruk. 10 Perdarahan perinatal yang juga berhubungan dengan luaran yang buruk 16 juga tidak ditemukan pada penelitian ini.…”
Section: Pembahasanunclassified